2016
DOI: 10.1016/j.healthpol.2016.03.009
|View full text |Cite
|
Sign up to set email alerts
|

How to ensure quality of health accounts

Abstract: Policy makers need up-to-date and reliable information to formulate health policies and monitor their implementation. Given that financing is one of the pillars of the health system, quality of financing data is essential. Quality is a key element but difficult to measure. Increasing quality on financing data involves the use of standard procedures and methods. Current standard framework, the System of Health Accounts 2011, needs to be implemented with checks and controls on the individual as well as aggregate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 7 publications
0
7
0
2
Order By: Relevance
“…Lopez-Casasnovas et al (2015), in an analysis of factors that complicate international comparisons of HCE across countries, observe that such comparisons may involve very different health systems in OECD countries with differing levels of development, and may not be informed by a clear policy question. Van Mosseveld et al (2016) observed that the quality of Health Accounts reporting for the SHA had been a concern for both producers and users and that this had implications for policy, since Health Accounts are produced to support decision-making. Among proposals for improving quality was to make the process more transparent and thereby enhance the accessibility of reports and cooperation between stakeholders (Van Mosseveld et al, 2016).…”
Section: The Development Of the Oecd's System Of Health Accountsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lopez-Casasnovas et al (2015), in an analysis of factors that complicate international comparisons of HCE across countries, observe that such comparisons may involve very different health systems in OECD countries with differing levels of development, and may not be informed by a clear policy question. Van Mosseveld et al (2016) observed that the quality of Health Accounts reporting for the SHA had been a concern for both producers and users and that this had implications for policy, since Health Accounts are produced to support decision-making. Among proposals for improving quality was to make the process more transparent and thereby enhance the accessibility of reports and cooperation between stakeholders (Van Mosseveld et al, 2016).…”
Section: The Development Of the Oecd's System Of Health Accountsmentioning
confidence: 99%
“…Van Mosseveld et al (2016) observed that the quality of Health Accounts reporting for the SHA had been a concern for both producers and users and that this had implications for policy, since Health Accounts are produced to support decision-making. Among proposals for improving quality was to make the process more transparent and thereby enhance the accessibility of reports and cooperation between stakeholders (Van Mosseveld et al, 2016). Mueller and Morgan (2017), while highlighting advances in the revised 2011 SHA accounting framework comprehensively implemented for the first time in 2016, acknowledged 'there is still some way to go to achieve full coverage and comparability of data' (Mueller and Morgan, 2017, p. 769).…”
Section: The Development Of the Oecd's System Of Health Accountsmentioning
confidence: 99%
“…GHED data shows higher expenditure on health workers than our salary estimates from ILO indicate. Both the data published by the ILO and those obtained from the Global Health Expenditure Database are subject to measurement error, and they also both have numerous missing observations [26]. The GHED data includes expenditures that are not included in a more direct measurement of salary as drawn from ILOSTAT.…”
Section: Resultsmentioning
confidence: 99%
“…26 No. 7 -2020 an international standard framework that helps ensure consistency and comparability of results (7).…”
Section: Introductionmentioning
confidence: 99%